Gridded bathymetry from EM120 multibeam echosounder of R/V SONNE cruise SO175 (Gulf of Cadiz) - Paul Wintersteller; Stefanie Gaide (PANGAEA, 2019)
Between 12.11.2003 and 30.12.2003, bathymetric data was acquired in the Gulf of Cadiz during the R/V SONNE cruise SO175. The expedition aimed at a better understanding of the interaction between dynamic processes in a seismically active region with slow plate convergence. In the context of earthquake nucleation and subduction zone processes, the multidisciplinary research programme focused on physical and chemical behavior of sediments, pore water and fluids, exploration of the temperature field of the 1755 thrust earthquake event, the quantification of microbial activity, faunal assemblages, gas hydrates and the deployment of a long-term pressure probe. Bathymetric mapping with the multibeam echosounder (MBES) SIMRAD EM120 was utilized to image the nature of the Gibraltar Arc thrust wedge, a proposed subduction zone, and identify possible sampling sites. Sub-bottom profiling, seismic reflection imaging, heat flow measurements, the deployment of an Ocean Floor pore pressure system as well as video-guided systems and coring complemented the research programme. CI Citation: Paul Wintersteller (seafloor-imaging@marum.de) as responsible party for bathymetry raw data ingest and approval. Description of the data source: During the SO175 cruise, the hull-mounted multibeam echosounder (MBES) SIMRAD EM120 was utilized to perform bathymetric mapping. It allows to conduct surveys in water depths of up to 11,000 m. Two transducer arrays transmit frequency coded acoustic signals (11.25 to 12.6 kHz). Data acquisition is based on successive emission-reception cycles of the signal. While the emission beam has a dimension of 150° across and 2° along track, the reception is obtained from 191 overlapping beams with widths of 2° across and 20° along track. The beam footprint has a dimension of 2° by 2°. The beam spacing can be set to equidistant or equiangular. For further information on the system, consult: https://www.km.kongsberg.com/ During the cruise, an opening angle of 60-70° was used depending on the state of the sea, restricting the coverage to a maximum 14 km wide swath to gain a more continuous spacing of beams on the ocean floor. The spacing within these limits was controlled automatically by the echosounder system. To convert the recorded travel times into water depth, several sound velocity profiles were obtained with the shipboard CTD, providing a correction for ray bending for each beam. Depth is estimated from each beam by using the two-way travel time and the known beam angle known, and taking into account the ray bending due to refraction in the water column by sound speed variations. Combining phase and amplitude is used to provide measurement accuracy practically independent of the beam pointing angle. Responsible persons during this cruise / PI: Achim Kopf (akopf@marum.de) & Ingo Grevenmeyer (igrevemeyer@geomar.de) Description of data processing: Postprocessing and products were conducted by the Seafloor-Imaging & Mapping group of MARUM/FB5, responsible person: Paul Wintersteller (seafloor-imaging@marum.de). The open source software MB-System suite (Caress, D.W., and D.N. Chayes, MB-System Version 5.6, open source software distributed from the MBARI and L-DEO web sites, 2000-2012.) was utilized for this purpose. The data was corrected for the roll movement of the vessel. There were no tide, pitch and heave corrections. Using Mbeditviz, artefacts were cleaned manually. NetCDF (GMT) grids of the edited data as well as statistics were created with mbgrid. The published bathymetric grid of the EM120 during cruise SO175 has a resolution of 40 m. No total propagated uncertainty (TPU) has been calculated to gather vertical or horizontal accuracy. A higher resolution is, at least partly, achievable. All grids produced are retrievable through the PANGAEA database (www.pangaea.de). Chief Scientist: Achim Kopf (akopf@marum.de) CR: https://elib.suub.uni-bremen.de/ip/docs/ELibD1195_228.pdf CSR: https://www2.bsh.de/aktdat/dod/fahrtergebnis/2003/20050152.htm Raw data: not yet